PEMBANGUNAN DAN FEMINISASI TANAH DI INDONESIA (KAJIAN EKOFEMINISME GLOBAL) - Mardian Sulistyati (Pusat Studi Gender dan Anak (PSGA), Universitas Islam Negeri Syarif Hidayatullah, 2018)
Abstract. Until now, the development process in most Third World countries including Indonesia still places women as second-class citizens; while leaving a latent environmental crisis problem. This paper examines the influence of development practices through the face of mining corporations, and examines the experiences of the struggles of the people who are in the circle of power relations. The global ecofeminism approach of Vandana Shiva and Maria Mies is used as a linguistic nomenclature that helps explain each of the key words in concepts that have previously been tendered by the patriarchal power system. In the end, the value of ecofeminism as the ethics of life becomes a solutive choice to restore traditional and relational awareness that transcends the binary barriers of the human genitals, and transcends the boundaries of human egoism towards non-humans.Abstrak. Hingga kini, proses pembangunan di sebagian besar negara Dunia Ketiga termasuk Indonesia masih menempatkan perempuan sebagai warga kelas dua; sekaligus menyisakan problem krisis lingkungan yang laten. Tulisan ini mengkaji pengaruh praktik pembangunanisme melalui wajah korporasi tambang, serta mengkaji pengalaman perjuangan masyarakat yang berada di dalam lingkar relasi kuasa tersebut. Pendekatan ekofeminisme global Vandana Shiva dan Maria Mies digunakan sebagai nomenklatur linguistik yang membantu memaparkan setiap kata kunci dalam konsep- konsep yang sebelumnya telah tergenderkan oleh sistem kuasa patriarki. Pada akhirnya, nilai ekofeminisme sebagai etika kehidupan menjadi pilihan solutif untuk mengembalikan kesadaran tradisional dan relasional yang melampaui sekat-sekat biner kelamin manusia, serta melampaui sekat egoisme manusia terhadap non-manusia.